Characteristics, complications, and outcomes of early-stage cervical stump carcinoma: laparoscopy versus laparotomy. Issue 2 (February 2021) - Lu, Zhiying; Guo, Chenyan; Wang, Ting; Qiu, Junjun; Hua, Keqin
Objective: To compare the characteristics, surgical complications, and overall survival between patients undergoing laparoscopy versus laparotomy for treatment of early-stage cervical stump carcinoma. Methods: Patients with International Federation of Gynecology and Obstetrics (FIGO, 2009) stage IA2 to IIA2 cervical stump carcinoma who underwent laparoscopy or laparotomy in the Obstetrics and Gynecology Hospital of Fudan University from January 2000 to June 2018 were retrospectively reviewed. All patients' clinical characteristics, pathological features, complications, and follow-up data were retrieved. Results: Seventy-two patients were included in the analysis; 58 underwent laparoscopy and 14 underwent laparotomy. With respect to surgical complications, laparoscopy was associated with a significantly lower complication rate, less blood loss, a shorter operative time, and a higher hospitalization fee than laparotomy. Survival was not significantly different between the laparoscopy and laparotomy groups. Conclusions: Although survival was not significantly different between the two surgical approaches, the rate of surgical complications was much lower in the laparoscopy than laparotomy group.